22. EMBRACING ISLAMIC VALUES IN MEDICAL IMAGING: A COMPREHENSIVE APPROACH - Sharip, Hairenanorashikin; Ma’on, Siti Noorsuriani; Abdullah, Mohd Zulkifli (Journal of Islamic, Social, Economics and Development, 2024)
The integration of Islamic values into medical imaging signifies the incorporation of ethical and spiritual principles rooted in Islam into the field. This process aims to ensure that practice and knowledge within medical imaging align with Islamic ethics, values, and beliefs. Stemming from the historical context of addressing societal challenges in the Muslim community, the concept of "Islamization of Knowledge" emerged in the 1960s, emphasizing the amalgamation of Islamic principles with contemporary knowledge. While this concept has gained prominence in various fields, its application in medical imaging remains relatively unexplored. Despite the dominance of Western concepts in the field, efforts have been made to integrate Islamic perspectives into the medical imaging curriculum and patient-centered care, emphasizing the holistic development of professionals guided by Islamic teachings. The integration extends to radiation protection practice, where adherence to guidelines is perceived as a moral and virtuous act deeply rooted in Islamic ethics. Additionally, the concept of Islamic Personality (IP) provides a framework for personalizing radiation protection practice among Muslim professionals, emphasizing professional traits relevant to the field. This paper explores the integration of Islamic values in medical imaging through various approaches, highlighting the significance of aligning practice with Islamic principles for the welfare of patients and the broader community.